The impact of perioperative anesthesia management-induced immunosuppression on postoperative cancer recurrence and metastasis: a narrative review - Teng, Yaxin; Yin, Yanfang; Shi, Yanan; Zhao, Junhui; Sun, Meiyan; Zhao, Xiaoyong (Frontiers in Oncology, 2025)
Perioperative anesthesia management not only ensures safe and smooth surgery, but its potential immunomodulatory function has also triggered close attention from many researchers. Surgical/anesthetic drugs can cause immunosuppression characterized by decreased natural killer (NK) cell activity, suppression of helper T cell (Th1) function, and imbalance of pro-inflammatory factors. The immunosuppressive microenvironment allows residual cancer cells to evade recognition by the host immune system, resulting in proliferation and distant metastasis. Several retrospective studies have demonstrated an association between cancer patients receiving inhalation anesthesia and reduced recurrence-free survival compared with cancer patients receiving propofol anesthesia. Regional anesthesia techniques may reduce the risk of postoperative recurrence of certain cancers by reducing the amount of systemic opioids and mitigating surgical stress, which in turn may reduce the risk of recurrence after surgery. This review also discusses the effects of pain, blood transfusion, hypothermia, blood pressure, and psychological stress on postoperative metastatic recurrence and immune function in cancer patients. However, observational studies of cancer outcomes after radical surgery for many cancer types under different anesthesia techniques have reported conflicting results, and large, prospective, randomized clinical trials (RCTs) are needed to clearly optimize anesthesia strategies, and to provide new ideas for future efforts to minimize immunosuppression and improve the long-term survival of cancer patients through individualized anesthesia regimens.